Solubility Enhancement Technologies and Research Emerged - Patel, Arun (International Journal of Pharmaceutical & Biological Archive, 2017)
Solubility is the phenomenon of dissolution of solid in liquid phase to give a homogenous system. Solubility is one of the important parameter to achieve desired concentration of drug in systemic circulation for pharmacological response to be shown. Some drugs pose challenging problems in their pharmaceutical product development process because of their low solubility and dissolution rates. Poorly water soluble drugs often require high doses and enhancement in solubility and dissolution rate in their formulation development especially solid dosage forms such as tablets and capsules. Low aqueous solubility is the major problem encountered with formulation development of new chemical entities. Any drug to be absorbed must be present in the form of an aqueous solution at the site of absorption. Most of drugs weakly acidic and weakly basic with poor aqueous solubility. Several conventional methods and new emerging technologies have been developed for the improvement of the solubility of poorly watersoluble drugs include micronization, chemical modification, pH adjustment, solid dispersion, nanosuspension, Superdisantigrant, liquisolid technique, complexation, coâ€solvency, micellar solubilization, hydrotropic, salt formation etc. The purpose of this review article is to describe the techniques of solubilizaton for the attainment of effective absorption and improved bioavailability.